Dose-Intensified Stereotactic Ablative Radiation for Localized Prostate Cancer - Chen, Lily; Gannavarapu, Bhavani S.; Desai, Neil B.; Folkert, Michael R.; Dohopolski, Michael; Gao, Ang; Ahn, Chul; Cadeddu, Jeffrey; Bagrodia, Aditya; Woldu, Solomon; Raj, Ganesh V.; Roehrborn, Claus; et al. (Frontiers in Oncology, 2022)
Purpose Stereotactic ablative radiation (SAbR) has been increasingly used in prostate cancer (PCa) given its convenience and cost efficacy. Optimal doses remain poorly defined with limited prospective comparative trials and long-term safety/efficacy data at higher dose levels. We analyzed toxicity and outcomes for SAbR in men with localized PCa at escalated 45 Gy in 5 fractions. Methods and Materials Retrospective analysis of men from 2015-2019 with PCa who received linear-accelerator based SAbR to 45 Gy in 5 fractions, along with peri-rectal hydrogel spacer, fiducial placement, and MRI-based planning. Disease control outcomes calculated from end of treatment. Minimally important difference (MID) assessing patient reported quality life was defined as greater than ½ standard deviation increase in American Urological Association (AUA) symptom score after SAbR. Results Two-hundred and forty-nine (249) low, intermediate, and high-risk PCa patients with median follow up of 14.9 months for clinical toxicity were included. Acute urinary grade II toxicity occurred in 20.4% of patients. Acute grade II GI toxicity occurred in 7.3% of patients. For follow-up > 2 years (n=69), late GU and GI grade ≥ III toxicity occurred in 5.8% and 1.5% of patients, respectively. MID was evident in 31.8%, 23.4%, 35.8%, 37.0%, 33.3%, and 26.7% of patients at 3, 6, 12, 24, 36, and 48 months, respectively. Median follow-up for biochemical recurrence was 22.6 months with biochemical failure-free survival of 100% at 1 year (n=226) and 98.7% for years 2 (n=113) and 3 (n=54). Conclusions SAbR for PCa at 45 Gy in 5 fractions shows encouraging safety profile. Prospective studies with longer follow-up are warranted to establish this dose regimen as standard-of-care for PCa.